Community Visioning for Agroecological Practices and Transition Pathways in the Tunisian Agroecological Living Landscape "Kef-Seliana Transect" - Ouji, Mourad (National Agricultural Research Institute of Tunisia, 2022)
Community Visioning for Agroecological Practices and Transition Pathways in the Tunisian Agroecological Living Landscape "Kef-Seliana Transect".